2010
DOI: 10.4103/0973-1482.77106
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of serum malondialdehyde in oral cancer and precancer and its association with healthy individuals, gender, alcohol, and tobacco abuse

Abstract: Increased serum malondialdehyde in oral cancer and oral precancer would serve as a valuable marker for both preventive and clinical intervention, and may deserve further investigation for the early diagnosis, treatment, and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 0 publications
12
81
0
Order By: Relevance
“…Genetic aberrations caused by ST include activation of ras, uncommon in smokers but mutational hot spots in p53 encountered are similar to those in smokers (Warnakulasuriya and Ralhan, 2007). Previous studies have demonstrated that an aqueous ST extract when given in a single oral dose to experimental rats results in an superior induction of liver lipid peroxidation, hepatic DNA single strand breaks (apoptosis marker), and a marked augmentation in the urinary excretion of the lipid metabolites malondialdehyde, formaldehyde, acetaldehyde, and acetone (Bagchi et al, 1994;Bagchi, 1997;Chole et al, 2010;Ramya et al, 2011;Kurtul and Gökpınar, 2012). A previous study indicated that the acute exposure of HOK-16B cells to ST leads to cell death, at least in part, through oxidative stress via up-regulation of ASK1 and the JNK 1/2 and p38 signaling pathways.…”
Section: Oral Cancer and Shammah In Saudi Arabiamentioning
confidence: 99%
“…Genetic aberrations caused by ST include activation of ras, uncommon in smokers but mutational hot spots in p53 encountered are similar to those in smokers (Warnakulasuriya and Ralhan, 2007). Previous studies have demonstrated that an aqueous ST extract when given in a single oral dose to experimental rats results in an superior induction of liver lipid peroxidation, hepatic DNA single strand breaks (apoptosis marker), and a marked augmentation in the urinary excretion of the lipid metabolites malondialdehyde, formaldehyde, acetaldehyde, and acetone (Bagchi et al, 1994;Bagchi, 1997;Chole et al, 2010;Ramya et al, 2011;Kurtul and Gökpınar, 2012). A previous study indicated that the acute exposure of HOK-16B cells to ST leads to cell death, at least in part, through oxidative stress via up-regulation of ASK1 and the JNK 1/2 and p38 signaling pathways.…”
Section: Oral Cancer and Shammah In Saudi Arabiamentioning
confidence: 99%
“…There are different forms of clinical appearances of OLP including linear, annular, popular, reticular and plaque shape, also atrophic, erosive (ulcerative) and bullous lesions in oral spaces at different periods or similar (Scully, Carrozzo, & Cartan, 2008). There are many studies in oxidative state of biological systems including production of ROS, oxidative stress and antioxidant defense, inflammation and chronic diseases that have been studied in degenerative and carcinogenesis disease (Ergun et al, 2011;Chole et al, 2010;Agha-Hosseini et al, 2009). The first step of production of oxidative stress is the metabolic reactions that use oxygen and represent disturbance balance in pro-oxidant/antioxidant reactions in living organisms (Valko et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…MDA is a major genotoxic carbonyl compound generated by lipid peroxidation and during arachidonic acid metabolism for the synthesis of prostaglandins. Hence, MDA levels are used to indicate oxidative and cellular damage to tissues due to ROS and free radicals (9,11).…”
Section: Introductionmentioning
confidence: 99%